Policy innovation and change: the diffusion and modification of the renewable portfolio standard, 1994 – 2014 - Hoffer, Katherine Anne Heriot, author; Davis, Charles E., advisor; Cheng, Antony, committee member; Moore, Scott T., committee member; Saunders, Kyle L., committee member (Colorado State University. Libraries, 2018)
To date, the U.S. federal government has not enacted a national renewable energy policy. Inertia at this level of government creates a policy space that allows American states to take the lead. State policy drives clean energy development. By the fall of 2014, every state in the nation had adopted at least one policy supportive of increased market penetration of renewable energy, and 38 states had adopted either a mandatory renewable portfolio standard (RPS) or a voluntary renewable energy goal. Between January 1, 1995 and the end of 2014, over 207 legislative changes amended existing RPSs and voluntary goals. Of these, most made small modifications or increased renewable energy requirements. Far fewer made significant changes to weaken state policy. This dissertation contributes to our understanding of energy policy innovation and change, where the adoption of an innovation is defined as a policy that is new to the state adopting it. It does so using a mixed methods approach that answers two major research questions: Why do states adopt different types of renewable portfolio standards (RPSs), while others fail to adopt any type of RPS? And, after states adopt an RPS, why do they amend the policy in the manner that they do over time? Using case studies and event history analysis based on a unified model of policy innovation suggested by existing literature, this study finds that both the size and direction of the effects of explanatory variables as well as the individual variables themselves vary across decision types, time, and space. More specifically, while the results confirm that household incomes, citizen and government ideology, and educational attainment are important internal state characteristics for explaining decisions to adopt and amend RPSs, the effect of these variables varies across different types of decisions. In addition, renewable energy interests and resources, fossil fuel resources and related interest groups, policy entrepreneurs, collaboration, and coalition building are important for explaining policy adoption and change. While this study found little to suggest that renewable energy potential is an important predictor of the decision to adopt an RPS, it did find that other state and federal policies are significant factors influencing the decision to adopt a certain type of RPS or amend an RPS in a certain manner. While the results of the case studies suggest that policy diffusion also plays an important role in explaining policy innovation and change, the results of the quantitative models must be interpreted with some caution.
Keywords: policy diffusion; renewable energy; state policy; policy innovation; energy; renewable portfolio standard